KAMPANYE PENINGKATAN PENGETAHUAN MAHASISWA UNDIP, UDINUS, DAN UNIKA SOEGIJAPRANATA TERHADAP BUS WISATA KOTA SEMARANG SEBAGAI ALTERNATIF STRESS RELIEF DALAM PERSPEKTIF MEDIA PLANNER, LOGISTIK, DAN VIDEOGRAFER - Aliyyanda Bulan putri; Adi Nugroho (Interaksi Online, 2026)
This study aims to analyze the effectiveness of the Bus Wisata Kota Semarang program as an alternative stress relief for university students. The research focuses on strategiesemployed by the media planner, logistics/production team, and videographer to enhancestudent awareness and engagement. Data were collected through surveys, social mediaanalytics, and direct observation of events such as Roadshow to Campus, Car Free Day preevents,special holiday events, and theTreasure Hunt main event.Findings show that integrated offlineand online communication strategies, including collaboration with media partners,Instagram Ads, and Key Opinion Leaders (KOLs), successfully increased student knowledgeand participation. Specifically, 84.2% of students answered mini-game questions correctlyduring campus roadshows, while social media engagement grew with 28 content posts,follower increase from 2,718 to 3,806, reach of 99,142, and an engagement rate rise from4.41% to 5.89%. The results indicate that a structured, consistent, and multimedia-basedcampaign can effectively promote the Bus Wisata Kota Semarang program, supportingstudents’ stress relief while strengthening public awareness of local tourism.